Importância das enzimas fibrolíticas na alimentação de vacas leiteiras: revisão bibliográfica - Nardo, Priscila Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The use of digestive enzymes has been gaining considerable space in the dairy sector, with the aim of promoting greater performance and animal health. One of the goals of using exogenous fibrolytic enzymes is to improve the nutritional value of forage for ruminants. Increasing fiber digestibility using exogenous enzymes can lead to significant improvements in ruminant performance in many parts of the world, particularly in tropical and subtropical regions. The effects of exogenous fibrolytic enzymes are influenced by many factors such as type and dose of enzyme, type of diet administered to animals and method of application of the enzymes, among others. Often when dairy cows are fed with such enzymes, there is an increase in the consumption of dry matter, digestibility of the fibrous portions, however, there is not always an increase in milk production or even an improvement in the chemical composition of the milk.

A utilização de Enzimas digestivas vem ganhando um espaço considerável no setor de pecuária leiteira, com intuito de promover maior desempenho e saúde animal. Um dos objetivos do uso de enzimas fibrolíticas exógenas é melhorar o valor nutritivo da forragem para ruminantes. O aumento da digestibilidade da fibra usando enzimas exógenas pode levar a melhorias significativas no desempenho de ruminantes em muitas partes do mundo, principalmente nas regiões tropicais e subtropicais. Os efeitos das enzimas fibroliticas exógenas são influenciados por muitos fatores tais como tipo e dose da enzima, tipo de dieta administrada aos animais e método de aplicação das enzimas entre outros. Muitas vezes quando vacas leiteiras são alimentadas com tais enzimas, ocorre aumento no consumo de matéria seca, digestibilidade das porções fibrosas, no entanto, nem sempre ocorre aumento na produção de leite ou mesmo melhora na composição química do leite.
Importance of fibrolytic enzymes in the feeding of dairy cows: bibliographic review
Keywords: Aditivos; Bovino; Forragem; Energia; Fibras; Bovino de leite